Fundamentals of queueing theory - Gross, Donald (J. Wiley & Sons, 2008)
This updated and expanded edition of Fundamentals of Queueing Theory presents the analytic modeling of queues in a very accessible style using up-to-date examples. Though the detailed coverage of the fundamentals of analytic modeling remains virtually the same, scores of new material have been added to reflect the most recent approaches to the topic. Additionally, in the treatment of the advanced material, the authors have commingled mathematical details with numerical results and intuitive arguments.